NUTRIENTS INTAKE AND OVARIAN PROFILE AS AFFECTED BY CATIONIC ANIONIC DIETS IN NILI-RAVI BUFFALOES DURING WINTER - M. Sharif; M. A. Shahzad; M. Nisa; M. Sarwar (Journal of Animal and Plant Sciences, 2012)
The study was conducted to investigate the potential of cationic and anionic diets, on nutrients intake, involution period, ovarian activity, follicle growth and uterus tonicity in early lactating buffaloes during winter. Twelve early lactating buffaloes were randomly divided into four groups, three buffaloes in each. Four isocaloric and isonitrogenous diets were formulated to have -110, +110, +220 and +330 dietary cation anion difference (DCAD) mEq/kg dry matter and mar Ked as A, LC, MC and HC diet, respectively. Diet allocation to four groups was random. A linear increase in dry matter intake (DMI) was observed with increased DCAD level. Maximum and minimum DMI was observed in buffaloes fed HC and A diets, respectively. Similar trend was followed by crude protein, neutral detergent fiber and acid detergent fiber. Rectal palpation on 40th day post partum revealed that buffaloes fed HC diet had completed uterus involution period while buffaloes fed A and LC diets didn’t complete involution period. Higher uterus tonicity was palpated in buffaloes fed HC diet compared to those receiving A, LC and MC diets. Lower ovarian activity was noticed in buffaloes fed A diet while its reverse was true in buffaloes on HC diet. Observed presence of corpus luteum in buffaloes fed HC diet was also higher in buffaloes fed HC diet. The findings of the present study indicated that high DCAD diet (HC diet) not only increased nutrients intake but also reduced involution period increased ovarian activity and uterus tonicity in early lactating buffaloes during winter.
Keywords: DCAD; nutrients intake; ovarian activity; follicle growth; lactating buffalo